Current concepts of PLP and its role in the nervous system - Griffiths, Ian; Klugmann, Matthias; Nave, Klaus-Armin (Microscopy research and technique, 1998)
Proteolipid protein (PLP) and its smaller isoform DM20 constitute the major myelin proteins of the CNS. Mutations of the X-linked Plp gene cause the heterogeneous syndromes of Pelizaeus-Merzbacher disease (PMD) and spastic paraplegia (SPG) in man and similar dysmyelinating disorders in a range of animal species. A variety of mutations including missense mutations, deletions, and duplications are responsible. Missense mutations cause a predicted alteration in primary structure of the encoded protein(s) and are generally associated with early onset of signs and generalised dysmyelination. The severity of the phenotype varies according to the particular codon involved and the influence of uncharacterised modifying genes. There is some evidence that the dysmyelination results from the altered protein acquiring a novel function deleterious to the oligodendrocyte's function. Transgenic mice carrying extra copies of the Plp gene provide a valid model of PMD/SPG due to gene duplication. Depending on the gene dosage, the phenotype can vary from early onset of severe and lethal dysmyelination through to a very late onset of a tract-specific demyelination and axonal degeneration. Mice with a null mutation of the Plp gene assemble and maintain normal amounts of myelin but develop a progressive axonopathy, again demonstrating tract specificity. The results indicate that the functions of PLP are far from clear. There is good evidence that it is involved in the formation of the intraperiod line of myelin, and the results from the knockout and transgenic mice suggest a role in the interaction of oligodendrocyte and axon.
Gesehen am 01.06.2017